Population genomics of yeasts: towards a comprehensive view across a broad evolutionary scale. Issue 3 (19th January 2016) - Peter, Jackson; Schacherer, Joseph
Abstract: With the advent of high‐throughput technologies for sequencing, the complete description of the genetic variation that occurs in populations, also known as population genomics, is foreseeable but far from being reached. Explaining the forces that govern patterns of genetic variation is essential to elucidate the evolutionary history of species. Genetic variation results from a wide assortment of evolutionary forces, among which mutation, selection, recombination and drift play major roles in shaping genomes. In addition, exploring the genetic variation within a population also corresponds to the first step towards dissecting the genotype–phenotype relationship. In this context, yeast species are of particular interest because they represent a unique resource for studying the evolution of intraspecific genetic diversity in a phylum spanning a broad evolutionary scale. Here, we briefly review recent progress in yeast population genomics and provide some perspective on this rapidly evolving field. In fact, we truly believe that it is of interest to supplement comparative and early population genomic studies with the deep sequencing of more extensive sets of individuals from the same species. In parallel, it would be more than valuable to uncover the intraspecific variation of a large number of unexplored species, including those that are closely and more distantly related. Altogether, these data would enable substantially more powerful genomic scans for functional dissection. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Yeast population genomics represents a unique opportunity to study the evolution of intraspecific diversity in species spanning a broad evolutionary scale. Recent surveys of genome‐wide polymorphism in different model and non‐model yeasts have enhanced insight into the evolutionary histories, the forces involved in genome evolution, and the relation between genotype and phenotype.